If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -2x + -2 = 10x + 3 + 2 Reorder the terms: 15 + -2 + -2x = 10x + 3 + 2 Combine like terms: 15 + -2 = 13 13 + -2x = 10x + 3 + 2 Reorder the terms: 13 + -2x = 3 + 2 + 10x Combine like terms: 3 + 2 = 5 13 + -2x = 5 + 10x Solving 13 + -2x = 5 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 13 + -2x + -10x = 5 + 10x + -10x Combine like terms: -2x + -10x = -12x 13 + -12x = 5 + 10x + -10x Combine like terms: 10x + -10x = 0 13 + -12x = 5 + 0 13 + -12x = 5 Add '-13' to each side of the equation. 13 + -13 + -12x = 5 + -13 Combine like terms: 13 + -13 = 0 0 + -12x = 5 + -13 -12x = 5 + -13 Combine like terms: 5 + -13 = -8 -12x = -8 Divide each side by '-12'. x = 0.6666666667 Simplifying x = 0.6666666667
| 102.74=-1.4-3.37(-3.5n-2.85) | | x+7+6x=91 | | 7x^2-24x-55= | | 1/3x=3x-4/5 | | -30+3y=90 | | 7[6-9(x-1)]+4[(5x+2)-3]=11x-341 | | 12y+38=10 | | (1-4x)/e^4x=0 | | 7+4x-x=16 | | -n-3.16(3.83n+1.6)=-94.17 | | 5z=4y | | -2(5y-5)-y=-4(y-4) | | x-7y=15-x | | -89.08=-4(4.87x+.33) | | 12=-n-2n | | -24.7938=9.7+x | | 6(2x-7)(3x+7)=0 | | 44=3y+11 | | 10.6375=5.75(a+1.2) | | 7y-8=3y-12 | | 450/8= | | -2+7x=2x+8 | | (-12)=w/4 | | x^2-4z=0 | | 18X-5Y-9X+Y= | | x^4-4x^3-20x^2-80x+208=0 | | M=D+Drt | | n/(-2)=-15 | | 7-0.2x=54 | | -9-5x=-1+3x | | 3x=4+-1y | | g(x)=x^3findg(2y) |